Exploring Pathways for the Connotative Development of Public Affairs Management in Aviation Universities - Yin, Junjie (Journal of Educational Research and Policies, 2025)
Amid China’s strategic transition from a “large civil aviation country” to a “strong civil aviation country,” the aviation industry is undergoing a historic shift from scale expansion to quality enhancement. From the perspective of governance modernization, this study conducts an in-depth analysis of the core principles and practical challenges in the connotative development of Public Affairs Management at aviation universities, and systematically constructs development pathways tailored to the aviation sector. The findings indicate that connotative development necessitates a paradigm shift: from emphasizing scale to focusing on quality, from knowledge indoctrination to competency cultivation, from discipline-oriented to demand-driven approaches, and from singular to multidimensional evaluation mechanisms. In response to current challenges—such as homogenized training objectives, outdated curriculum systems, monotonous teaching methods, insufficient faculty expertise, and misaligned evaluation mechanisms—this paper proposes comprehensive reforms across five dimensions: objective positioning, curriculum restructuring, pedagogical innovation, faculty development, and quality assessment. The study aims to provide theoretical insights and practical guidance for the transformation and upgrading of Public Affairs Management in aviation universities.